KONSEP MANAJEMEN PENDIDIKAN KARAKTER DALAM MENUMBUHKAN AKHLAKUL KARIMAH DI MTS RAUDHATUL ISLAMIYAH KEMIRI - A, Asnawati (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2021)
This paper discusses the concept of management of character education in MTs Raudhatul Islamiyah Kemiri, the concept in question is the pattern of character growth of students with various supporting elements such as madrasa activities, rules or regulations, and content of Islamic education lessons that are applied in MTs Raudhatul Islamiyah Kemiri. In addition to these supporting elements, in order to grow the character of morality also has several strategies in supporting the achievement of character education management concepts such as: exemplary, learning, empowerment and acculturation, retention, and assessment. At this time Character becomes important for human life, especially for the next generation of nation. Therefore character education becomes important in school. However, the achievement of character values must be applied with good management. Character education management is a planned effort to make learners recognize, care and internalize the values so that learners are able to grow its character that consists of the process of planning, organizing, implementation and supervision.